Health Education about Food Safety based on Hazard Analysis and Critical Control Points (HACCP) at Selera Kita Restaurant in Kuwait - Nurwijayanti; Zulkipli Abdullah Usin; Laily Nurhanifah (Journal of Community Engagement in Health, 2024)
The prospect of food business in the form of restaurants in Kuwait is quite promising. This is because many native Kuwaitis and immigrants often use restaurant services. Restaurant performance must meet consumer expectations so that they feel satisfied as users of the restaurant's products. To maintain and increase satisfaction, restaurants must pay attention to food management activities in restaurants so that they run in accordance with applicable regulations. A series of activities starting from menu planning, food distribution to consumers to achieve optimal health status through providing appropriate food including recording, reporting and evaluation is a series of food management. Based on the results of initial observations and interviews with managers, employees and consumers at the Selera Kita restaurant in Kuwait, this community service aims to find strategic ways by providing education related to management, employees and consumers' understanding of food safety based on Hazard Analysis and Critical Control Points (HACCP), knowing several variables which are strengths, weaknesses, opportunities and threats, knowing strategies that can be taken by management to improve service to consumers. Respondents were selected using a simple random sample. The results of this research are in the form of health education about food safety based on Hazard Analysis and Critical Control Points (HACCP) with assessments using Fishbone diagrams, SWOT analysis and descriptive analysis showing that 70% of the 30 respondents have sufficient knowledge of food safety to improve services to consumers has been implemented well, but needs to be improved so that it can run more optimally.